2007
DOI: 10.1248/cpb.55.477
|View full text |Cite
|
Sign up to set email alerts
|

Bithiazole Metabolites from the Myxobacterium Myxococcus fulvus

Abstract: The myxobacteria have produced a wide variety of structurally unique secondary metabolites.1) Of the myxobacteriaderived metabolites, bithiazole-containing compounds e.g. myxothiazoles, [2][3][4] cystothiazoles, 5,6) and melithiazoles, 7) exhibit potent antimicrobial activity, cytotoxicity and inhibition of mitochondrial respiration which have attracted considerable attention for synthetic, biochemical, and related studies. [8][9][10][11][12][13] During the course of our search for bioactive compounds from myx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…As it is still unknown whether any metabolite derived from a ΔclbP mutant actually represents a precursor to a genotoxin, the relevance of these two distinct electrophilic warheads for colibactin’s biological activity is unclear. The bithiazole motif found in 7 is also observed in the DNA damaging metabolite bleomycin and several myxothiazol metabolites . Planar bithiazole rings are thought to intercalate into duplex DNA by making π-stacking interactions within the purine-pyrimidine backbone .…”
Section: Resultsmentioning
confidence: 82%
“…As it is still unknown whether any metabolite derived from a ΔclbP mutant actually represents a precursor to a genotoxin, the relevance of these two distinct electrophilic warheads for colibactin’s biological activity is unclear. The bithiazole motif found in 7 is also observed in the DNA damaging metabolite bleomycin and several myxothiazol metabolites . Planar bithiazole rings are thought to intercalate into duplex DNA by making π-stacking interactions within the purine-pyrimidine backbone .…”
Section: Resultsmentioning
confidence: 82%
“…Ahn et al . [46] studied the effect of pH value on antifungal metabolites produced by a Myxococcus isolate and found that a pH value between 6.5 and 7.6 was favored and the optimal pH value was 7.2.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cystothiazole A was active against many fungal strains, including Candida albicans (MIC 0.4 μg/mL), but inactive against the tested bacterial strains [103]. Myxothiazoles (Figure 9), isolated from Myxococcus fulvus cultures, showed moderate antifungal activity against the Candida albicans strain [104]. Comparing cystothiazole A with myxothiazole A, it could be observed that the former was more active and less cytotoxic [103].…”
Section: Antimicrobial Activitymentioning
confidence: 99%